HUBUNGAN PENGETAHUAN DENGAN PERILAKU SEKSUAL PADA REMAJA DI SMK MJPS 1 KOTA TASIKMALAYA - Reni Nurdianti; Lina Marlina; Sumarni Sumarni (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2021)
Nowadays, sex among teenagers is not taboo. Sexual behavior among adolescents tends to increase, especially unmarried adolescents. In the24 countries in North America and Europe show that adolescent sexual behavior begins at the age of 15. The survey was conducted to 33,943 in 24 countries carried out by a French Non-Governmental Organization (NGO), showing that 13.2% of adolescents have been sexually active since the age of 15 and do not use contraceptives. Meanwhile, 82% use contraception.The purpose of this study was whether there was a relationship between knowledge and sexual behavior in adolescents at SMK MJPS 1 Tasikmalaya city. This research method is descriptive analytic with cross-sectional correlation approach. Samples taken in this study were students of class X-XII teenagers at SMK MJPS 1 Tasikmalaya city by using the sampling technique used was random sampling. The results of the respondent's data taken were 89 people. From the data obtained, students with sufficient knowledge amounted to 60 people or (67.4%) and a small number of students with less knowledge amounted to 7 people (7.9%) with less behavior amounted to 37 people or (41.6%) and good behavior amounted to 24 people or (27%). Statistical test results obtainedx²= 15.922, p-value 0.003 <0.05 means that there is a relationship between knowledge and sexual behavior in adolescents at SMK MJPS 1 Kota Tasikmalaya. Based on the results of the study, there is a need for education and counseling for adolescents by the local health center regarding the impact of sexual behavior on adolescents.